Answer:
(6,-2)
Explanation:
Given equations are and .
Solve 2nd equation for y
...(i)
Plug value of y from equation (i) into first equation
Plug x=6 into equation (i)
Hence final answer is x=6, y=-2 or we can write that in (x,y) form as (6,-2)
2x + 3y = 6
x + y = 4
Multiply the second equation by -2 to eliminate x
-2(x+y) = -2*4
-2x-2y = -8
Add this to the first equation
-2x -2y = -8
---------------------
y = -2
Now we need to find x
x+y = 4
x-2 = 4
Add 2 to each side
x-2+2 = 4+2
x = 6
5.2m questions
6.8m answers